740 Seasonal influenza vaccination in health care workers and students. survey in a large italian university hospital. (24th April 2018) - Belingheri, M; Riva, MA; Turato, M; De Vito, G; D'Orso, MI; Latocca, R; Cesana, G
Abstract : Introduction: Vaccination is an important measure for preventing influenza. Its importance in healthcare settings is twofold: it does not only protects Health Care Workers (HCWs) – possibly reducing disease-related work absenteeism and the consequent disruption of health services – but vulnerable patients too. The aim of the study was to evaluate the influenza vaccination coverage among HCWs and students in a large Italian university hospital. Methods: We collected data on influenza vaccination among HCWs and healthcare students in the period 2012–2016. Data included sex, age, work unit, and job title (HCWs)/degree course (students). We applied chi-square test and t-test for statistical comparisons. The level of significance adopted was 5%. Result: In the analysed period, a total of 2218 vaccines were administered, with a progressive increase from 302 (2012) to 659 (2016) per year (mean ±SD: 444±150). Focusing on 2016, 49.3% of the vaccinated subjects were students or residents, 42.0% HCWs, 7.0% administrative staff and 1.7% volunteers. Among HCWs, the mean age of the vaccinated subjects was higher than the mean age of all hospital staff (49.5 vs 45.9, p-value<0.05). Men were more vaccinated than women (12.3% vs 7.6%, p-value<0.05). The highest vaccination coverage was among medical doctors (21.3%), followed by administrative staff (8.7%), nurses and midwives (6.5%), and other healthcare workers (3.4%). Among students, the highest vaccination coverage was in medical students (33.2%), followed by nursing and midwifery students (8.2%), and other healthcare students (6.3%). Conclusion: In Italy, the increasing flu vaccination rates was likely due to the growing public concern regarding infectious diseases, particularly meningococcal meningitis. Older HCWs were the most vaccinated, probably because age and its related disorders raise awareness on the importance of vaccination. In this sense, they use vaccination in order to protect themselves. The higher vaccination coverage among doctors and medical students suggests an important influence of education.